2018
DOI: 10.17794/rgn.2018.5.6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of River Sava Temperature Influence on Groundwater Temperature of the Zagreb and Samobor-Zaprešić Aquifer as a Part of Shallow Geothermal Potential

Abstract: Based on the statistical analysis of the time series of data, the infl uence of the change of the Sava River temperature on the changes of the groundwater temperature of the Zagreb and Samobor-Zaprešić aquifers is described. In the analysis, data was used from daily measurements of the Sava River temperature and from the quarterly measurements of the groundwater temperature. Statistical methods of correlation and linear regression were applied and the maximum, mean and minimum groundwater temperatures were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The Zagreb aquifer is designated as a part of a strategic water reserve, protected by the Republic of Croatia, which represents the main source of potable water for the citizens of the City of Zagreb and part of Zagreb County. In recent years, in the wider area of the City of Zagreb, numerous research projects have been performed, primarily isotopic, mostly focused on the following: the evaluation of nitrates' origin in the Zagreb aquifer [27], the influence of the Sava River temperature on the groundwater temperature [28], groundwater-surface water interaction between the Sava River and the Zagreb aquifer [6], the estimation of groundwater velocities [29], the evolution of Zagreb's Local Meteoric Water Line (LMWL), and changes in meteorological variables [16], as well as the examination of hillslope soil hydrology [30]. It has been shown that soil type can have big influence on precipitation infiltration [6], but also that a constant increase in mean annual air temperature is evident.…”
Section: Introductionmentioning
confidence: 99%
“…The Zagreb aquifer is designated as a part of a strategic water reserve, protected by the Republic of Croatia, which represents the main source of potable water for the citizens of the City of Zagreb and part of Zagreb County. In recent years, in the wider area of the City of Zagreb, numerous research projects have been performed, primarily isotopic, mostly focused on the following: the evaluation of nitrates' origin in the Zagreb aquifer [27], the influence of the Sava River temperature on the groundwater temperature [28], groundwater-surface water interaction between the Sava River and the Zagreb aquifer [6], the estimation of groundwater velocities [29], the evolution of Zagreb's Local Meteoric Water Line (LMWL), and changes in meteorological variables [16], as well as the examination of hillslope soil hydrology [30]. It has been shown that soil type can have big influence on precipitation infiltration [6], but also that a constant increase in mean annual air temperature is evident.…”
Section: Introductionmentioning
confidence: 99%
“…They observed a very weak correlation of measured δ 18 Ο values between Plitvica stream and the waters from the piezometers 2500 and 4039 and attribute it to the drainage role of the Plitvica stream in this part of the aquifer. Kapuralić et al (2018) analysed Sava River temperatures and groundwater temperatures by statistical methods of correlation and linear regression for the development of shallow geothermal energy applications. Generally, statistical methods are used both in fractured and/or karstic aquifers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The overall length of all installed borehole heat exchangers (BHE) is at least 55 km at the end of 2020. Additionally, the use of groundwater in open type heat pump systems is currently at a capacity of 13.7 MW t (Kapuralić et al, 2018).…”
Section: Introductionmentioning
confidence: 99%